GANGGUAN KOGNITIF PENDERITA PENYAKIT PARKINSON - Fatma Adhayani, Dina Listyaningrum, Hasan Sjahrir (NEURONA, 2014)
INTRODUCTION THE HIGH LIPID LEVEL HAD BEEN KNOWN TO PLAY A ROLE IN THE DEVELOPMENT OF ALZHEIMER DISEASE AD IN AD MEMORY IMPAIRMENT WAS THE EARLIEST AND THE MOST AFFECTED ASPECT